2018
DOI: 10.1177/1098300718796788
|View full text |Cite
|
Sign up to set email alerts
|

Group Video Self-Modeling to Improve the Classroom Transition Speeds for Elementary Students

Abstract: Teachers who are effective classroom and behavior managers must master a range of strategies and skills, and an essential component is developing and implementing effective strategies for students to transition between activities (Hine, Ardoin, & Foster, 2015). Smooth and quick transitions help decrease wasted time. Schmit, Alper, Raschke, and Ryndak (2000) found that approximately 25% of daily time is taken for transition activities for elementary and preschool children. Jones and Jones (2010) stressed that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…It was found that learners were encouraged to model positive behaviour by giving some learners responsibilities to lead different clubs that were offered in schools and others were engaged as peer counsellors. The results of this study correspond with literature revelation that peer modelling helps the individual learn by having others perform an appropriate version of the behaviour (McNiff, 2015). The findings of the study also support the results of Mukiri's (2014) study in Kenya which revealed that prefects enhanced maintenance of discipline to a greater extent as they modelled positive behaviour to other learners.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…It was found that learners were encouraged to model positive behaviour by giving some learners responsibilities to lead different clubs that were offered in schools and others were engaged as peer counsellors. The results of this study correspond with literature revelation that peer modelling helps the individual learn by having others perform an appropriate version of the behaviour (McNiff, 2015). The findings of the study also support the results of Mukiri's (2014) study in Kenya which revealed that prefects enhanced maintenance of discipline to a greater extent as they modelled positive behaviour to other learners.…”
Section: Discussionsupporting
confidence: 87%
“…Also, peers can either positively or negatively influence the behaviour of learners. Literature reveals that peer modelling helps the individual learn by having others perform an appropriate version of the behaviour (McNiff, 2015). According to Tungata (2006) learners or children in general, worship their heroes and imitate those whom they appreciate and admire.…”
Section: Introductionmentioning
confidence: 99%
“…There is an emerging research base on the use of videos in PBIS implementation (McNiff, Maag, & Peterson, 2019). At this time, the amount of research and accompanying positive outcomes documenting use of videos in PBIS implementation does not allow for video use to be considered an evidence-based practice for students with EBD according to the criteria specified by Horner et al (2005).…”
Section: A Rationale For Pbis Video Usementioning
confidence: 99%
“…Group video self-modeling (GVSM) is an extension of VPM and VSM allowing for multiple familiar persons to be included in the instructional aspect. In a recent study, McNiff and colleagues (2019) utilized GVSM in an elementary classroom to improve transition speeds while lining up and moving from one activity to another. Results indicated that GVSM was practical, efficient, and successful, which led McNiff and colleagues (2019) to assert that GVSM as a meaningful way to teach groups of students PBIS behaviors and expectations.…”
Section: A Rationale For Pbis Video Usementioning
confidence: 99%
“…Another form is group video-modeling. As the term implies, a group of individuals is engaged in the desired behavior (e.g., a group of students moving quickly and quietly from one classroom to another) (McNiff et al 2019).…”
Section: Introductionmentioning
confidence: 99%